Management of Malignant Pleural Effusion: Where Are We Now? - Guinde, Julien; Dutau, Hervé; Astoul, Philippe (Seminars in Respiratory and Critical Care Medicine, 2022)
Pleural malignancies are among the most common causes of pleural disease and form the basis of our daily pleural practice. There has been significant research and increase in both diagnostic and therapeutic management of malignant pleural diseases in the last decade. Good-quality data have led to a paradigm shift in the management options of pleural malignancies, and indwelling pleural catheter is now recommended and widely used as first-line intervention. Several trials compared different treatment modalities for pleural malignancies and continue to emphasize the need to reduce hospital length of stay and unnecessary pleural intervention, and the importance of patient choice in clinical decision making. This practical review aims to summarize the current knowledge for the management of pleural malignancies, and the understanding of the steps that we still have to climb to optimize management and reduce morbidity.
Keywords: pleural effusion; pleural malignancy; talc; indwelling pleural catheter; thoracoscopy